Vehicle-mounted charger shell with rapid heat dissipation - AN YAN; LI SHIBING; JI ZHENGLEI; HU YAN (2024)
The utility model discloses a vehicle-mounted charger housing with rapid heat dissipation, which relates to the technical field of vehicle-mounted chargers, and comprises a housing, a fixed cover is arranged at the upper end of the housing, first bolt seats are fixedly connected to two ends of two sides of the upper part of the housing, second bolt seats are fixedly connected to two ends of two sides of the fixed cover, and the first bolt seats and the second bolt seats are fixedly connected to the fixed cover. And each group of second bolt seats corresponds to one group of first bolt seats, and the middle parts of each group of corresponding second bolt seats and first bolt seats are in bolted connection with bolts. Air penetrates through the drying box and enters the middle of the shell, so that water vapor is absorbed by the drying agent, the air entering the middle of the shell is drier, electronic devices in the middle of the shell are prevented from being affected with damp, the motor drives the fan bla